Value of additional lateral radiographs in paediatric skeletal surveys for suspected physical abuse. Issue 1 (January 2022) - Meshaka, R.; Garbera, D.M.; Arthurs, O.J.; Shelmerdine, S.C.
Abstract : Aim: To determine the added value of lateral limb radiographs in suspected physical abuse (SPA), particularly with regard to fracture detection and reporter confidence. Methods and materials: A 3-year (October 2017 to November 2020) retrospective study was conducted. Two blinded paediatric radiologists independently reviewed the appendicular radiographs for the presence of fractures, first by reviewing just the frontal projections, then both frontal and lateral radiographs. The additional yield of fractures and changes in reporting confidence scores were recorded. Results: One hundred and thirty-eight skeletal surveys (29 live, 109 deceased children) were assessed, consisting of 16 appendicular fractures imaged in two projections (six wrist, five knee, five ankle). In the majority of cases (14/16) the fractures were already visible on the frontal view with only two fractures (one distal radius, one distal tibial) identified only by lateral projection on the blinded review. One fracture (distal tibia) was visible only on the frontal radiograph (not lateral view). The addition of lateral projection did not lead to overcalling of fractures in the remaining normal studies. Radiologist confidence scores showed an improvement with the addition of a lateral projection when a study was thought to be normal ( p= 0.001–0.003), but not when a fracture was identified ( p> 0.05). CONCLUSION: The addition of lateral radiographs improves reporting confidence in normal skeletal surveys, but only rarely helped to detect additional fractures given that most were visible on frontal projections. Larger multicentre studies of clinical practice are required to confirm these findings. Highlights: Fractures in SPA are rarely identified on the lateral view alone. Lateral views did not improve diagnostic confidence when a fracture was seen on AP. Lateral views did increase radiologists' confidence when the AP view was normal.